Reconstruction of the University Model: Transition to the Model 5.0 - Nguyễn Phan Anh (Journal of Technical Education Science, 2025)
This paper analyzes the development of university models from 1.0 to 4.0, combined with a comparison of higher education digitalization policies in the United States, Germany, and China, as well as Japan’s vision for Society 5.0, to propose the university 5.0 model. The distinctive feature of university 5.0 lies in the integration of modern technologies such as artificial intelligence (AI), the Internet of Things (IoT), and big data with green culture and social responsibility to create a sustainable educational ecosystem. The university 5.0 model transcends the limitations of a digital university by not only optimizing educational processes but also promoting personalized learning, developing emotional-social skills, and fostering environmental responsibility. Furthermore, this model enables flexible connections between physical and virtual spaces, while encouraging collaboration among universities, governments, and businesses to address global challenges. The research findings confirm that university 5.0 represents an inevitable evolution in the era of technology and sustainability, placing humans at the center and providing a theoretical framework for implementation in modern education.